L2/FL Teacher Education: Bridging the complexities of Teaching and the Learning of Teaching - Karen E. Johnson; Adriana de C. Kuerten Dellagnelo (Ilha do Desterro)
Research on approaches to and the complexities of second and foreign language (L2/FL) teaching has dominated the field of L2/FL teacher education for much of its history. (...)